Avaliação dos efeitos da saliva dos carrapatos das espécies Amblyomma sculptum, Amblyomma parvum e Rhipicephalus sanguineus sobre linhagens celulares tumorais de mama humanas e murina - Sousa, Ana Carolina Prado (2015)
Cancer remains one of the most troubling diseases with increasing occurrence. Breast cancer has a great chance of cure when diagnosed early, but in most cases, its late diagnosis leads to patients a treatment often painful and devastating. The search for new alternative treatments, that can make it more effective and less harmful, has led to several substances and biomolecules of plants and animals with anti-tumor activity. Ticks present in their saliva different molecules with different properties, which are immunomodulatory, anticoagulants, anti-inflammatory, and also showed some anti-tumor effects across different tumor cell lines. This study aimed to evaluate the effect of the saliva of ticks of the species Rhipicephalus sanguineus, Amblyomma parvum and Amblyomma sculptum on cell lines of breast cancer MCF-7, MDA-MB-231 and Ehrlich cells. It can be seen that the three different types of front saliva showed cytotoxicity to tumor cells did not demonstrate the same effect on non tumor cell. Morphological changes were also observed on the surface of tumor cell lines, which did not occur in the MCF-10A cells. Furthermore, it was found that tumor cells to die by apoptosis and that these cells, check for the presence of caspase-3 activity / 7, suggesting the possible occurrence of apoptosis by the intrinsic pathway. These changes were not observed in MCF10A cells, which remained broadly unchanged even after exposure to different types of saliva. These results suggest that tick saliva is a potential source for the development of new breast cancer drugs.